PENGGUNAAN MEDIA PEMBELAJARAN KARTU KUARTET PERISTIWA DAN TOKOH SEJARAH MATERI SEJARAH KONTEMPORER PADA MAHASISWA JURUSAN PENDIDIKAN SEJARAH DAN SOSIOLOGI DI IKIP BUDI UTOMO MALANG - Irvan Lestari; Muhammad Naharuddin Arsyad (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT Teaching and learning activities should not only be carried out conventionally, such as lecturers lecturing and students listening. Learning history must have variations in its implementation, the use of media can be one way so that teaching and learning activities are not monotonous. Because history is the study of the past and historical narratives demand to be explained chronologically. Thus, a quartet card containing pictures of events and historical figures that are conceptualized in accordance with historical proclamation, is expected to be able to facilitate the delivery of contemporary historical material as well as learning activities to be active. The purpose of this study was to determine the effectiveness of the use of learning media quartet cards events and historical figures. This type of research is an experimental method, with one group pretest posttest design research design. From the results of the Kolmogorov-Smirnov test using SPSS 14 it was found that the research subjects were normally distributed and based on the results of the Paired Samples Test t-test it was found that the sig value was 0,000> 0.05. While the t -10.921 and for ttable at a significant level α = 5% (0.05) with degrees of freedom (df) n-1 or 45-1 = 44. 2-sided testing (significance = 0.025) results are obtained for ttable at 2, 01537 with a significant level of 0.025. Obtained the results of -test <-table (-10,921 <-2,01537) then H0 is rejected and Ha is accepted. So it can be concluded that the use of Learning Media Quartet Cards Events and Historical Figures Contemporary History Materials can improve the learning outcomes of students majoring in history and sociology IKIP Budi Utomo Malang. Keywords: Quartet Card Media, Contemporary History, Learning Outcomes